2020
DOI: 10.3390/diagnostics10110990
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Calprotectin Concentrations with Mortality in Critically Ill and Septic Patients

Abstract: Background: Calprotectin is present in the cytosol of neutrophil granulocytes and released upon activation. Fecal calprotectin is applied in the clinical management of inflammatory bowel disease whereas serum calprotectin has been discussed as a biomarker in inflammatory disorders. However, its long-term prognostic relevance in critical illness remains unclear. Our aim was to investigate serum calprotectin concentrations as a prognostic biomarker in critically ill and septic patients. Methods: Serum calprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…It has recently been reported that calprotectin can be used as a biomarker of inflammation for assessing the activity of some inflammatory disorders. 34 In addition, according to that study, a significant elevation of serum calprotectin was associated with high mortality in Covid-19 patients. 35 Studies are ongoing, but there is not enough evidence at this time to support this finding and no scientific consensus whether calprotectin can serve as a prediction of how serious the virus will be in some patients.…”
Section: Discussionmentioning
confidence: 85%
“…It has recently been reported that calprotectin can be used as a biomarker of inflammation for assessing the activity of some inflammatory disorders. 34 In addition, according to that study, a significant elevation of serum calprotectin was associated with high mortality in Covid-19 patients. 35 Studies are ongoing, but there is not enough evidence at this time to support this finding and no scientific consensus whether calprotectin can serve as a prediction of how serious the virus will be in some patients.…”
Section: Discussionmentioning
confidence: 85%
“…In patients with SARS-COVID-19 infection receiving treatment in an intensive care unit, the ROC assay results indicated that MRP8/14 was superior to other markers (ferritin, CRP, lactate dehydrogenase) in evaluations of the patient’s health status [ 54 ]. Wirtz reported that mortality of SARS-COVID-19 patients in intensive care units was related to a reduction in MRP8/14 levels, whereas the surviving subjects had increased MRP8/14 levels [ 55 ]. This could explain the finding of lower MRP8/14 concentrations in exposed men vs. the men in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 14 ] Conditions other than COVID-19 have also showed elevated serum calprotectin levels like critically ill patients, critical patients with sepsis, and is associated with renal and respiratory dysfunction and predicts long term mortality risk. [ 28 29 ] Another study showed higher levels in COVID-19 patients requiring mechanical ventilation. [ 20 ] These observations and the fact that calprotectin was raised in deceased patients [ Table 2 ] in our study suggest its possible role in prediction of critical illness and death.…”
Section: Discussionmentioning
confidence: 99%